The Processing of English Derived Words by Chinese‐English Bilinguals. Issue 4 (28th June 2017) - Li, Junmin; Taft, Marcus; Xu, Joe
Abstract: This study examined the sensitivity of Chinese‐English bilinguals to derivational word structure in English. In the first experiment, English monolinguals showed masked priming effects for prime‐target pairs related both transparently (e.g., hunter ‐ HUNT ) and opaquely (e.g., corner ‐ CORN ) but not for those related purely in terms of form (e.g., freeze‐FREE ), whereas bilinguals showed priming in all three conditions. Furthermore, stronger form priming was found for bilinguals who were less experienced in English. A second experiment showed that bilingual participants found it harder to identify items as nonwords when the words possessed a suffix (e.g., animalful ) than when they did not (e.g., animalfil ), and this was true in terms of accuracy even for bilinguals with less exposure to English. Overall, these findings suggest that Chinese‐English bilinguals, regardless of proficiency, have some sensitivity to morphological structure and that greater proficiency leads to priming effects that tend to pattern more like those of monolinguals.